Disembedding and re-embedding practices of social innovation at the nexus of migration and labour exploitation in agriculture - Palmioli, Lucia; Dentoni, Domenico; Brunori, Gianluca (Frontiers in Sustainable Food Systems, 2024)
The last two decades have witnessed growing academic debate on labour exploitation, caporalato, organised crime and migration issues in agriculture which, as wicked problems, are deeply interconnected and resist generalizable solutions. To contribute to this thriving debate from a social innovation lens, we investigate the organising practices meant to disrupt the organised statusquo of exploitation. Drawing upon a case study from Foggia, in Puglia (southern Italy), we investigate how an Italian non-profit organisation developed and implemented a multi-stakeholder pilot project of economic integration in rural areas to confront the phenomenon of labour exploitation in agriculture. Through collaboration among authorities, civil societies, and private sectors, this pilot project managed to unlock underused resources to meet the needs of the most vulnerable individuals embedded in the local ecosystem. By developing a grounded theory on practices of dis-embedding and embedding, this paper contributes to theories on social innovation as political actions and interactions that purposely trigger disruption in established systems of labour exploitation, organised crime and migration.